VESSELS STUDY OF SOME MEDICINAL PLANTS Dr. Chavan (International Journal of Food and Nutritional Sciences, 2022)
The study of vascular anatomy in plant species provides essential insights into their physiologicaladaptations, ecological roles, and potential applications in pharmacology and medicine. This study focuses onthe comparative analysis of the vascular structures of Maerua oblongifolia, Marsdenia volubilis andSansevieria roxburghiana. Maerua oblongifolia and Marsdenia volubilis two climber species known for theirmedicinal properties. Both species belong to distinct families, Capparaceae and Apocynaceae, respectively, butexhibit similar growth habits and environments, making them suitable for comparative vascular analysis.Sansevieria roxburghiana belongs to family Agavaceae. Histological examinations were conducted on thestems and roots of each species to observe the arrangement, size, and distribution of xylem and phloem tissues.Maerua oblongifolia was found to possess well-developed xylem vessels adapted for efficient water transport,a feature likely beneficial for survival in arid conditions. Conversely, Marsdenia volubilis exhibited a denserphloem network, which may support its climbing habit and facilitate nutrient distribution across its elongatedstructure.The study concludes that while these three species have unique vascular adaptations related to their growthforms and environmental demands, these structural characteristics also contribute to their medicinalapplications. The vascular structures likely play a role in the synthesis and storage of bioactive compounds.Findings from this comparative analysis of Maerua oblongifolia, Marsdenia volubilis and Sansevieriaroxburghiana used for electuary in consumptive complaints and chronic cough of long standing contribute tothe broader understanding of plant vascular anatomy and its implications for botanical pharmacology, ecology,and sustainable medicinal plant use.